2015
DOI: 10.1158/1541-7786.mcr-14-0262
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Somatic Chromosomal Copy Number Aberrations in GEM Models of Prostate Carcinoma

Abstract: Human prostate cancer (PCa) is known to harbor recurrent genomic aberrations consisting of chromosomal losses, gains, rearrangements and mutations that involve oncogenes and tumor suppressors. Genetically engineered mouse (GEM) models have been constructed to assess the causal role of these putative oncogenic events and provide molecular insight into disease pathogenesis. While GEM models generally initiate neoplasia by manipulating a single gene, expression profiles of GEM tumors typically comprise hundreds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Thus, while activation of MYC alone or disruption of Pten alone result in very early disease, the combination of these two events synergize in creating profound changes leading to highly aggressive disease that progresses from PIN precursor lesions, to invasive adenocarcinoma, to metastatic adenocarcinoma, and ultimately castration resistant metastatic adenocarcinoma. Since these primary tumors develop highly prevalent CNAs, and neither alteration alone results in significant numbers of CNAs (36, 43), we show the first evidence in vivo that the combination of Pten loss and MYC activation in prostatic luminal cells is sufficient to induce the acquisition and tolerance of genetic instability, independent of forced telomere dysfunction or loss/mutation of Tp53. MYC overexpression is known to induce genetic instability (44), and our results suggest that PTEN serves to repress this process in prostate cells.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, while activation of MYC alone or disruption of Pten alone result in very early disease, the combination of these two events synergize in creating profound changes leading to highly aggressive disease that progresses from PIN precursor lesions, to invasive adenocarcinoma, to metastatic adenocarcinoma, and ultimately castration resistant metastatic adenocarcinoma. Since these primary tumors develop highly prevalent CNAs, and neither alteration alone results in significant numbers of CNAs (36, 43), we show the first evidence in vivo that the combination of Pten loss and MYC activation in prostatic luminal cells is sufficient to induce the acquisition and tolerance of genetic instability, independent of forced telomere dysfunction or loss/mutation of Tp53. MYC overexpression is known to induce genetic instability (44), and our results suggest that PTEN serves to repress this process in prostate cells.…”
Section: Discussionmentioning
confidence: 80%
“…Despite two decades of effort to develop mouse prostate cancer models, all extant models have at least one of the following limitations: i) they are driven by alterations in genes not commonly found to be genetically altered in human prostate cancer, or; ii) do not develop widespread metastatic disease, or; iii) develop prominent histological features not commonly found in human prostate cancer (e.g. small cell neuroendocrine or sarcomatoid differentiation); or iv) generally do not develop significant numbers of genomic alterations/genetic instability in the absence of forced telomere dysfunction (2224). Additionally, since most genetically engineered models of prostate cancer rely on forced androgen driven oncogene expression, these models are limited when exploring the effects of castration/androgen deprivation, since such treatments necessarily result in direct repression of the transgene, which in turn generally leads to growth suppression (22).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been relatively difficult to model metastatic prostate cancer, particularly bone metastasis, which is a major metastatic site in human patients (Irshad and Abate-Shen 2013). Finally, the frequent chromosomal rearrangements and extensive intratumoral heterogeneity observed in advanced human prostate cancers are not observed in many GEM prostate cancer models (Bianchi-Frias, et al 2015; Wanjala, et al 2015). However, a recent study has reported high frequencies of genomic alterations and intratumoral heterogeneity in the PB-Cre4; Pten flox/flox ; Trp53 flox/flox model (Wanjala et al 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Although very rare, bone metastases have also been observed, similar to human prostate cancer. Importantly, the prostate cancers that develop in the BMPC mice have widespread genome copy number alterations, a feature that is reminiscent of human disease, and not recapitulated in most other well‐studied prostate cancer mouse models . For instance, one of the only other mouse models demonstrating genomic instability required forced telomere shortening in the context of Tp53 and Pten deletion .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the prostate cancers that develop in the BMPC mice have widespread genome copy number alterations, a feature that is reminiscent of human disease, and not recapitulated in most other well-studied prostate cancer mouse models. [23][24][25][26][27] For instance, one of the only other mouse models demonstrating genomic instability required forced telomere shortening in the context of Tp53 and Pten deletion. 28 However, mice with combined Tp53 and Pten deletion commonly develop invasive prostatic tumors with sarcomatoid differentiation rather than adenocarcinoma.…”
mentioning
confidence: 99%